2017
DOI: 10.2460/javma.250.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Use of a subdermal plexus flap to reconstruct an upper eyelid following radical tumor resection in a cat

Abstract: CASE DESCRIPTION A 15-year-old neutered male domestic shorthair cat was examined for treatment of a recurrent neoplastic mass in the left upper eyelid that had been excised 6 months earlier by the referring veterinarian. CLINICAL FINDINGS An apparently nonpainful firm cutaneous mass (approx 2 × 2 mm) was located on the lateral third of the left upper eyelid near the scar from the previous surgical excision. TREATMENT AND OUTCOME Approximately one-third of the left upper lip was used as a subdermal plexus (lip-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…First choice of treatment of Eyelid tumor is surgical excision and repair/reconstruction of the eyelid as soon as possible. 4 With the improvement of living standard and medical technology in recent years, people pay more and more attention to appearance, which also raises the relevant standard requirements of traditional eye surgery.…”
Section: Discussionmentioning
confidence: 99%
“…First choice of treatment of Eyelid tumor is surgical excision and repair/reconstruction of the eyelid as soon as possible. 4 With the improvement of living standard and medical technology in recent years, people pay more and more attention to appearance, which also raises the relevant standard requirements of traditional eye surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Three case reports of feline basal cell carcinoma exist in the veterinary literature. Two of the case reports did not have metastasis at the time of diagnosis and the cats did well without local recurrence or metastasis after local therapy alone 6,7 . To the authors’ knowledge, there is only one case report from 1994 describing metastasis of basal cell carcinoma in one of two cats 8 .…”
Section: Introductionmentioning
confidence: 96%
“…Two of the case reports did not have metastasis at the time of diagnosis and the cats did well without local recurrence or metastasis after local therapy alone. 6,7 To the authors' knowledge, there is only one case report from 1994 describing metastasis of basal cell carcinoma in one of two cats. 8 The cat had pulmonary nodules present on radiographs at the time of initial presentation for a facial basal cell carcinoma, and metastasis to the mandibular lymph node was confirmed histologically at the time of surgical removal.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Subsequent reports have provided evidence to support the application of this compound flap for upper and lower eyelid reconstruction precipitated by trauma, tumor resection, and feline eyelid agenesis with a variation adapted for closure of defects involving the hard palate. [3][4][5][6] The musculofascial island labial flap also is a variation of this technique used to reconstruct the canine nose after nasal planectomy. 7 Use of the lip-to-lid procedure for nasal reconstruction was initially reported in the dog.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that the mucocutaneous subdermal plexus flap (termed the lip‐to‐lid procedure ) has been effective when the entire lower eyelid is reconstructed in dogs and cats 1,2 . Subsequent reports have provided evidence to support the application of this compound flap for upper and lower eyelid reconstruction precipitated by trauma, tumor resection, and feline eyelid agenesis with a variation adapted for closure of defects involving the hard palate 3‐6 . The musculofascial island labial flap also is a variation of this technique used to reconstruct the canine nose after nasal planectomy 7 .…”
Section: Introductionmentioning
confidence: 99%